Setting oral health goals that include oral health-related quality of life measures: a study carried out among adolescents in Thailand Incorporação da qualidade de vida relacionada à saúde bucal em metas de saúde bucal: estudo conduzido em adolescentes tailandeses - Sudaduang Krisdapong; Piyada Prasertsom; Khanit Rattanarangsima; Supreda Adulyanon; Aubrey Sheiham (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to assess the association between oral diseases and condition-specific oral health-related quality of life (CS-OHRQoL) as a basis for proposing OHRQoL-based goals for the population of 15-year-olds in Thailand. Oral examinations and OHRQoL interviews were conducted with 871 15-year-olds as part of the Sixth Thailand National Oral Health Survey. The severity of oral impacts was categorized using "intensity". Associations between oral diseases and CS-OHRQoL were analyzed using chi-square and logistic regression. Thirty-nine percent of 15-year-olds experienced moderate/higher levels oral impacts on quality of life. Compared to those individuals with no tooth decay, adolescents with one or four or more decaying teeth were three and seven times more likely to experience moderate/higher impacts, respectively. Adolescents with extensive gingivitis in 3 or more mouth sextants were twice as likely to experience moderate/higher CS-impacts. Based on these findings, it is proposed that goals should focus on untreated decaying teeth and extensive gingivitis. Oral health goals for 15-year-olds should include specific OHRQoL measures. O objetivo deste estudo foi avaliar a associação entre doença bucal e a condição específica de qualidade de vida associada à saúde bucal (CS-OHRQoL), como base para propor OHRQoL metas para adolescentes tailandeses. Exame clínico bucal e entrevista foram realizados em 871 adolescentes na faixa etária de 15 anos, como parte da 6ª Pesquisa Nacional Tailandesa de Saúde Bucal. A severidade do impacto bucal foi categorizada usando-se a "intensidade". A associação entre doença bucal e CS-OHRQoL foi investigada usando-se o teste qui-quadrado e regressão lógica. Trinta e nove por cento da amostra reportaram impactos bucais de grau moderado/elevado. A probabilidade de reportar um impacto bucal de grau moderado/elevado dos adolescentes com um dente cariado e aqueles com 4 ou mais foi 3 e 7 vezes maior, respectivamente, quando comparada à dos adolescentes sem dentes cariados. A presença de gengivite severa em 3 ou mais sextantes dobrou a probabilidade de ocorrência do CS-impacto de grau moderado/elevado. Metas de saúde bucal para adolescentes devem incluir instrumentos específicos de OHRQoL.